Research Progress of Genetic Structure, Pathogenic Mechanism, Clinical Characteristics, and Potential Treatments of Coronavirus Disease 2019 - Zhu, Chunsheng; Sun, Bao; Zhang, Xiaochuan; Zhang, Bing (Frontiers in Pharmacology, 2020)
Coronavirus disease 2019 (COVID-19) is a global pandemic infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), and currently affects more than 8 million people worldwide. SARS-CoV-2 mainly invades the cells by binding to the angiotensin converting enzyme 2 (ACE2) receptor, leading to the injury of respiratory system, cardiovascular system, digestive system, and urinary system, and even secondary to acute respiratory distress syndrome (ARDS) and systemic inflammatory response, resulting in multiple organ failure. In this review, mainly focusing on biogenesis and pathogenic mechanisms, we describe the recent progress in our understanding of SARS-CoV-2 and then summarize and discuss its crucial clinical characteristics and potential mechanism in different systems. Additionally, we discuss the potential treatments for COVID-19, aiming at a better understanding of the pathogenesis of SARS-CoV-2 and providing new ideas for the personalized treatment of COVID-19.